Catchment instability and Asian summer monsoon variability during the early Holocene in southwestern China. (24th October 2012) - Cook, Charlotte G.; Jones, Richard T.; Turney, Chris S. M.
<x xml:space="preserve">Abstract</x> A high‐resolution palaeorecord (06SD) from Lake Shudu, Yunnan Province, southwestern China indicates a broad trend towards catchment stability, enhanced organic productivity and regional forest‐cover expansion during the early to mid Holocene. These changes are congruent with a shift to warm, wet climatic conditions, probably driven by orbitally forced Asian summer monsoon strengthening. Intriguingly, however, during the very early Holocene (c. 10.7 to 10.1 cal. ka BP), there is a prominent reversal in this trend, suggesting a weakening Asian summer monsoon. The precise cause and extent of this event remain unclear but demonstrate the urgent need for more comprehensive dating of records from across the region to test for synchroneity and examine climatic forcing mechanisms.